TRAINING DESIGN TO ENHANCE SERVICE QUALITY IN HOLLAND BAKERY - Maharani Joner, Agistya
The bakery industry in Indonesia has seen increased demand in recent years. The market is being driven by increased disposable incomes and shifting consumer demands for convenience and health. The bread category in the Indonesian market has experienced an annual growth rate of 4.98% according to the Compound Annual Growth Rate (CAGR) for the period of 2023-2027. It is projected to reach a value of US$ 11.92 billion by 2023. The revenue is projected to experience a 39.9% growth in 2023. Meanwhile, Indonesia’s bread sector is projected to experience a volume growth of 5.7% by 2024, reaching a volume of 9,398.8 million kilograms by 2027. Local bakeries in Indonesia frequently establish a prominent presence in smaller towns and rural areas, cultivating loyal customers over a long time. These bakeries frequently provide a diverse range of local breads and pastries, which can be a significant factor in attracting customers. Bread is expected to be the largest and fastest-growing segment in terms of kind. Bread’s popularity comes from its widespread consumption by people of all ages. The competition between the local and franchise bread industries is intense, with each having unique business models that come with their own strengths and weaknesses. The ultimate success of a bakery depends on critical elements such as product quality and service quality. In response to this growing market, bakery companies need to differentiate themselves not just through their products but also through the quality of service they provide. As the market becomes more competitive, delivering excellent service becomes a key factor in attracting and retaining customers. In the fast-moving consumer goods retail market, excellent service is the highest priority that has the potential to enhance customer loyalty and sustain or even increase sales rates. By providing exceptional services, bakeries can set themselves apart from competitors and ultimately attract customers who value these services. Holland Bakery, a pioneer bakery company in Indonesia, established in 1978 under PT Mustika Citra Rasa, holds the same belief on the importance of providing exceptional service. Holland Bakery’s commitment to excellence is not only for product quality but also excellent customer service standards. The belief that their frontline personnel serve ii as a reflection of their business, consequently it is crucial to provide them with education to enhance the level of service. The research was conducted to assess service quality components that need improvement using the 5-dimensions of the SERVQUAL model - reliability, responsiveness, assurance, empathy, and tangible- captured both perspective of customer and employee. The author uses research methods with data collection tools in the form of questionnaires and interviews. A mix-method of quantitative-qualitative using descriptive statistics, importance performance analysis (IPA) and thematic analysis on 205 customers and 125 employees of Holland Bakery indicate several elements of service quality that still need improvement which are handling customer complaints, consistency in providing service quality, product knowledge, promotion skills, responsiveness, attitude, prompt delivery, accuracy of product and transaction detail information, delivering specific customer request, communication skills and selfconfidence. From these elements, the deficiency of current training and aspirations for future training are developed. The gap in these elements is used to create business solutions in the form of training design and curriculum to enhance employees’ competencies in service quality to better serve the customer.